Wear-resistant antifouling hardened film and preparation process thereof

By using a specific formula anti-fouling hardening coating liquid and precision coating process to prepare a wear-resistant anti-fouling hardening film, the problem that the prior art cannot meet multiple wear-resistant standards at the same time is solved, and the effect of high wear resistance and high water contact angle is achieved.

CN119591922APending Publication Date: 2025-03-11JIANGSU RIJIU OPTOELECTRONICS LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411727308.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The existing wear-resistant hardened films cannot meet multiple wear-resistant standards at the same time, such as eraser wear-resistant standards and steel wister ball wear-resistant standards.

Method used

Anti-fouling hardening coating liquid including photocured acrylic acid resin, acrylate monomer, metal oxide particles, antistatic agents, surfactants, antifouling agents and photoinitiators is used to prepare wear-resistant and antifouling hardening films through precision coating processes and ultraviolet curing technology.

Benefits of technology

The wear resistance of the hardened film is improved, so that it can meet a variety of wear resistance standards, such as the eraser wear resistance tests exceeding 2000 times, and the water contact angle (≥101°) is maintained after 1000 times.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119591922A_ABST
    Figure CN119591922A_ABST
Patent Text Reader

Abstract

The invention discloses a wear-resistant anti-fouling hardened film and a preparation process thereof, the wear-resistant anti-fouling hardened film comprises a base material layer and an anti-fouling hardened layer arranged on one side surface of the base material layer; the anti-fouling hardened layer is prepared from an anti-fouling hardened coating liquid through a precise coating process, and the anti-fouling hardened coating liquid is prepared from the following raw material components in parts by mass: 20 to 30 parts of light-cured acrylic resin, 15 to 20 parts of acrylate monomers, 2 to 6 parts of metal oxide particles, 1.5 to 4 parts of an antistatic agent, 0.3 to 0.8 part of a surfactant, 1 to 3 parts of an anti-fouling agent, 2 to 4 parts of a photoinitiator and 30 to 55 parts of a solvent; an eraser wear resistance test of the antifouling hard coating film reaches 2000 times or more, and after the eraser wear resistance test reaches 1000 times or more, a water contact angle of the antifouling hard coating film reaches 101 degrees or more. According to the wear-resistant antifouling hard coating film and the preparation process thereof, the wear resistance of the hard coating film can be improved, and various wear-resistant standards can be met at the same time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of hardened protective films, and in particular relates to a wear-resistant and antifouling hardened film and a preparation process thereof. Background Art

[0002] With the continuous development of electronic technology, the development of flat panel display technology is also constantly improving, and the requirements for optical-grade polyester films required for the surface of decorative panels in display devices, equipment and instruments are becoming higher and higher, from the initial protective function to the later requirements of various functional requirements such as high transparency, high hardness, high strength, and strong wear resistance.

[0003] It is widely used in various occasions such as consumer electronics, tablets, aircraft cabins, laptops and large monitors, etc., which require high performance. Since it is often necessary to write marks on the screen, it has very high requirements for its wear resistance. Therefore, a layer of hardened film needs to be pasted on its surface to meet the needs of wear-resistant use.

[0004] The existing wear resistance is generally expressed by the steel wool wear resistance standard, that is, the steel wool wear resistance is usually between 1000 and 2000 times. However, for specific usage scenarios, the wear resistance must not only meet the steel wool wear resistance standard, but also meet other wear resistance standards. For example, the eraser wear resistance standard must be ≥2000 times to meet the standard. The existing wear-resistant hardened film cannot meet multiple wear resistance standards at the same time.

[0005] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention and should not be regarded as an acknowledgment or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art. Summary of the invention

[0006] The object of the present invention is to provide a wear-resistant and anti-fouling hardened film and a preparation process thereof, which can improve the wear resistance of the hardened film and meet multiple wear resistance standards at the same time.

[0007] In order to achieve the above-mentioned object, a technical solution provided by a specific embodiment of the present invention is as follows: a wear-resistant and antifouling hardened film comprises a substrate layer and an antifouling hardened layer provided on one side of the substrate layer;

[0008] The antifouling hardening layer is prepared by a precision coating process of an antifouling hardening coating liquid, wherein the antifouling hardening coating liquid comprises the following raw material components by weight: 20 to 30 parts of a photocurable acrylic resin, 15 to 20 parts of an acrylic acid ester monomer, 2 to 6 parts of metal oxide particles, 1.5 to 4 parts of an antistatic agent, 0.3 to 0.8 parts of a surfactant, 1 to 3 parts of an antifouling agent, 2 to 4 parts of a photoinitiator, and 30 to 55 parts of a solvent;

[0009] The antifouling hardened film can withstand more than 2000 eraser abrasion tests, and after 1000 eraser abrasion tests, its water contact angle reaches more than 101°.

[0010] In one or more embodiments of the present invention, the photocurable acrylic resin is at least one of ethylene glycol diacrylate, 1,3-butanediol diacrylate, 1,4-butanediol diacrylate, 1,6-hexanediol diacrylate and 1,9-nonanediol.

[0011] In one or more embodiments of the present invention, the acrylate monomer is at least one of diacrylate, trimethylolpropane triacrylate, ditrimethylolpropane tetraacrylate, pentaerythritol triacrylate and dipentaerythritol hexaacrylate.

[0012] In one or more embodiments of the present invention, the metal oxide particles are at least one of nano-aluminum dioxide particles and nano-silicon dioxide particles.

[0013] In one or more embodiments of the present invention, the antistatic agent is at least one of polyethylene oxide, polyether ester amide, and polyquaternary ammonium salt.

[0014] In one or more embodiments of the present invention, the surfactant is at least one of an organosiloxane polymer, an acrylic polymer, an acrylic copolymer, a methacrylic polymer, and a methacrylic copolymer.

[0015] In one or more embodiments of the present invention, the antifouling agent is a modified perfluoropolyether containing unsaturated double bonds.

[0016] In one or more embodiments of the present invention, the photoinitiator is at least one of 1-hydroxycyclohexyl phenyl ketone, 2-methyl-1-(4-methylthiophenyl)-2-morpholinyl-1-propanone, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide and 2-hydroxy-methylphenylpropane-1-one.

[0017] In one or more embodiments of the present invention, the solvent is at least one of ethyl acetate, butanone, cyclohexanone, toluene, methyl isobutyl ketone, butyl acetate, methyl ethyl ketone, ethanol, isopropanol, methanol and propylene glycol monomethyl ether.

[0018] A specific embodiment of the present invention further provides a process for preparing the wear-resistant and antifouling hardened film as described above, comprising the following steps:

[0019] S1, adding metal oxide particles to a mixed system of acrylate monomer and solvent, and mixing them evenly to obtain a premixed solution;

[0020] S2, adding a photocurable acrylic resin, a photoinitiator, an antistatic agent, a surfactant and an antifouling agent to the premixed liquid, and mixing them evenly to obtain an antifouling hardening coating liquid;

[0021] S3, coating the antifouling hardening coating liquid on the substrate layer, and obtaining an incompletely cured wear-resistant antifouling hardened film after drying and first UV curing;

[0022] S4, subjecting the incompletely cured wear-resistant and antifouling hardened film to a second ultraviolet curing to obtain the antifouling hardened film;

[0023] Among them, nitrogen protection is required during the first UV curing in step S3 to control the oxygen concentration, and the oxygen concentration is ≤300ppm. Nitrogen protection is not required for the second UV curing in step S4.

[0024] Compared with the prior art, the wear-resistant and antifouling hardened film and its preparation process of the present invention enhance the wear resistance of the entire wear-resistant and antifouling hardened film by compounding the raw materials in the antifouling hardening coating liquid, especially through the interaction between surfactants, antistatic agents and metal oxide particles, thereby improving the wear resistance and meeting a variety of wear resistance standards, such as eraser wear resistance standards and steel wool wear resistance standards. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0026] Figure 1 Schematic diagram of the structure of the wear-resistant and anti-fouling hardened film in one example of the present invention.

[0027] Description of main reference numerals:

[0028] 1. Base material layer; 2. Antifouling hardening layer. DETAILED DESCRIPTION

[0029] In order to enable those skilled in the art to better understand the technical solutions in the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0030] like Figure 1As shown, the wear-resistant and antifouling hardened film in an example of the present invention comprises a substrate layer 1 and an antifouling hardened layer 2 arranged on one side of the substrate layer 1; the antifouling hardened layer 2 is made of an antifouling hardening coating liquid through a precision coating process, and the antifouling hardening coating liquid comprises the following raw material components by mass: 20 to 30 parts of photocurable acrylic resin, 15 to 20 parts of acrylic ester monomer, 2 to 6 parts of metal oxide particles, 1.5 to 4 parts of antistatic agent, 0.3 to 0.8 parts of surfactant, 1 to 3 parts of antifouling agent, 2 to 4 parts of photoinitiator, and 30 to 55 parts of solvent; wherein, the eraser wear resistance test of the antifouling hardened film reaches more than 2000 times, and after the eraser wear resistance test is 1000 times, its water contact angle reaches more than 101°.

[0031] It should be noted that the antifouling hardened layer 2 formed by designing the raw material formula of the antifouling hardened coating liquid can make the wear-resistant antifouling hardened film of the present invention meet the requirements of customers through the eraser wear resistance test and after 1000 times of the eraser wear resistance test, its water contact angle reaches more than 101°.

[0032] Preferably, the photocurable acrylic resin is at least one of ethylene glycol diacrylate, 1,3-butanediol diacrylate, 1,4-butanediol diacrylate, 1,6-hexanediol diacrylate and 1,9-nonanediol.

[0033] Preferably, the acrylate monomer is at least one of diacrylate, trimethylolpropane triacrylate, ditrimethylolpropane tetraacrylate, pentaerythritol triacrylate and dipentaerythritol hexaacrylate.

[0034] Preferably, the metal oxide particles are at least one of nano-alumina particles and nano-silicon dioxide particles. The nano-alumina particles can be selected from DK410-2 or DK410-1, and the brands UVH-D-AL-3 and UVH-D-AL-24 of Harima Chemicals Co., Ltd.; the nano-silicon dioxide particles can be selected from MEK-AC-4130Y, MEK-AC-5140Z, MIBK-SD-L, or FMNPSOH-W40 or FMNPSOH-W50 of Hualu New Materials.

[0035] The D90 particle size of the metal oxide particles can be 40 to 110 nm, preferably 40 to 50 nm. The purpose of adding metal oxide particles to the hardened film is mainly to improve the activity and stability of the catalyst and to improve the performance of the film, especially the metal oxide particles, surfactants and antistatic agents cooperate to enhance the wear resistance of the hardened film.

[0036] Preferably, the antistatic agent is at least one of polyethylene oxide, polyether ester amide, and polyquaternary ammonium salt. For example, Toyo Ink LAS1513-18. Antistatic agents mainly prevent sparks caused by friction, reduce or eliminate surface scratches caused by friction, improve the smoothness and roughness of the processed surface, improve the wear resistance of the workpiece surface, reduce cutting force, and reduce tool wear. These effects not only help to increase the service life of the film, but also improve its performance, making it more durable during use.

[0037] In addition, excessive addition of antistatic agent will interfere with touch control and affect touch control after conductivity. That is, antistatic agent can provide smoothness and wear resistance, but excessive addition will negatively affect the touch function.

[0038] Preferably, the surfactant is at least one of an organosiloxane polymer, an acrylic polymer, an acrylic copolymer, a methacrylic polymer and a methacrylic copolymer. For example, the surfactant may be KP341 (manufactured by Shin-Etsu Chemical Co., Ltd.), Polyflow No.75, Polyflow No.77, Polyflow No.90, Polyflow No.95 (manufactured by Kyoeisha Chemical Co., Ltd.), W001 (manufactured by Yusho Co., Ltd.), etc.

[0039] Surfactants can improve the smoothness, hydrophobicity and oleophobicity of the film surface; in addition, metal oxide particles, surfactants and antistatic agents cooperate to enhance the wear resistance of the hardened film.

[0040] Preferably, the antifouling agent is a modified perfluoropolyether containing unsaturated double bonds, such as the antifouling agent of OPTPPL produced by Jinfu Chemical Co., Ltd.

[0041] Preferably, the photoinitiator is at least one of 1-hydroxycyclohexyl phenyl ketone (photoinitiator 184), 2-methyl-1-(4-methylthiophenyl)-2-morpholinyl-1-propanone (photoinitiator 907), 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (photoinitiator 1110) and 2-hydroxy-methylphenylpropane-1-one (photoinitiator 1173).

[0042] Specifically, the photoinitiator may be selected from the substances produced by BASF, Evonik Degussa, and Nanjing Jiazhong Chemical Technology Co., Ltd.

[0043] Preferably, the solvent is at least one of ethyl acetate, butanone, cyclohexanone, toluene, methyl isobutyl ketone, butyl acetate, methyl ethyl ketone, ethanol, isopropanol, methanol and propylene glycol monomethyl ether.

[0044] Preferably, the substrate layer 1 can be an optical grade polyester film, because it not only has good processing and forming properties, but also has high light transmittance and low haze properties. For example, the substrate layer 1 is usually made of PET substrate or TAC substrate, and the thickness is usually 50μm, 125μm and 188μm according to different application requirements. The substrate layer 1 usually has a primer layer, that is, the substrate layer 1 directly purchased on the market (such as Toray U48, U40).

[0045] A specific embodiment of the present invention further provides a process for preparing the wear-resistant and antifouling hardened film as described above, comprising the following steps:

[0046] S1, adding metal oxide particles to a mixed system of acrylate monomer and solvent, and mixing them evenly to obtain a premixed solution;

[0047] S2, adding a photocurable acrylic resin, a photoinitiator, an antistatic agent, a surfactant and an antifouling agent to the premixed liquid, and mixing them evenly to obtain an antifouling hardening coating liquid;

[0048] S3, coating the antifouling hardening coating liquid on the substrate layer, and obtaining an incompletely cured wear-resistant antifouling hardened film after drying and first UV curing;

[0049] S4, subjecting the incompletely cured wear-resistant and antifouling hardened film to a second ultraviolet curing to obtain the antifouling hardened film;

[0050] Among them, nitrogen protection is required during the first UV curing in step S3 to control the oxygen concentration, and the oxygen concentration is ≤300ppm. Nitrogen protection is not required for the second UV curing in step S4.

[0051] Specifically, the above steps may include:

[0052] Take a PET substrate, apply the prepared antifouling hardening coating liquid on one side of the PET substrate layer at a temperature of 20°C to 25°C, then dry it at a temperature of 70°C to 130°C for 1 to 10 minutes, and then irradiate it under an ultraviolet high-pressure mercury lamp with an irradiation of 1200mJ / cm 2 , the antifouling hardening coating liquid is cured for 2 to 5 seconds (first UV curing) at a speed of 10 to 15 m / min to form an incompletely cured hardened layer, and a wear-resistant antifouling hardened film is initially obtained; during UV curing, nitrogen protection is required to control the oxygen concentration, and the oxygen concentration is ≤300ppm. By introducing nitrogen protection, the oxygen inhibition effect is achieved, thereby ensuring that the film layer has good hardness, adhesion and scratch resistance.

[0053] The wear-resistant and antifouling hardened film was irradiated with an ultraviolet high-pressure mercury lamp at a dose of 1000 mJ / cm 2, and irradiate and cure for 2 to 5 seconds (second UV curing) at a walking speed of 10 to 15 m / min to obtain the wear-resistant and antifouling hardened film of the present invention.

[0054] The wear-resistant and antifouling hardened film and its preparation process of the present invention will be described in detail below in combination with specific embodiments and comparative examples.

[0055] Example 1

[0056] 15 parts by mass of acrylate monomer (dipentaerythritol hexaacrylate) was added to a mixture of 25 parts by mass of propylene glycol monomethyl ether, 20 parts by mass of ethanol, and 5 parts by mass of methyl ethyl ketone, and 2 parts by mass of silicon oxide particles (MEK-AC-4130Y) with a particle size of 40 to 50 nm were added, and the mixture was fully stirred under an ultrasonic environment;

[0057] Then, 20 parts by mass of photocurable acrylic resin (15 parts by mass of ethylene glycol diacrylate, 5 parts by mass of 1,4-butanediol diacrylate), 2 parts by mass of photoinitiator 184, 1.5 parts by mass of Toyo Ink LAS1513-18, 0.3 parts by mass of organosiloxane polymer KP341 and 1 part by mass of perfluoropolyether (OPTPPL antifouling agent) were added to the mixed liquid and stirred thoroughly to obtain an antifouling hardening coating liquid.

[0058] The prepared antifouling hardening coating liquid was then coated on a PET substrate with a thickness of 125 μm, and then dried at a temperature of 80°C for 7 minutes, and then irradiated with an ultraviolet high-pressure mercury lamp at an ultraviolet radiation dose of 1200 mJ / cm 2 The antifouling hardening coating liquid was cured at a speed of 12 m / min for 5 seconds to form a hardened layer, and a wear-resistant antifouling hardened film was initially obtained. Nitrogen protection was required during UV curing to control the oxygen concentration. In this embodiment, the oxygen concentration was controlled at 150 ppm.

[0059] Then secondary UV curing, curing conditions: UV radiation is 1000mJ / cm 2 , and irradiated and cured for 2 seconds at a walking speed of 15 m / min to obtain the wear-resistant and anti-fouling hardened film of the present invention.

[0060] Example 2

[0061] 20 parts by weight of acrylate monomer (dipentaerythritol hexaacrylate) was added to a mixture of 15 parts by weight of propylene glycol monomethyl ether, 10 parts by weight of ethanol, and 5 parts by weight of methyl ethyl ketone, and 2 parts by weight of silicon oxide particles (MEK-AC-4130Y) with a particle size of 40 to 50 nm were added, and the mixture was fully stirred under an ultrasonic environment;

[0062] Then, 30 parts by mass of photocurable acrylic resin (1,9-nonanediol), 2 parts by mass of photoinitiator 184, 1.5 parts by mass of Toyo Ink LAS1513-18, 0.3 parts by mass of organosiloxane polymer KP341 and 1 part by mass of perfluoropolyether (OPTPPL antifouling agent) were added to the mixed liquid and stirred thoroughly to obtain an antifouling hardening coating liquid.

[0063] The prepared antifouling hardening coating liquid was then coated on a PET substrate with a thickness of 125 μm, and then dried at a temperature of 80°C for 7 minutes, and then irradiated with an ultraviolet high-pressure mercury lamp at an ultraviolet radiation dose of 1200 mJ / cm 2 The antifouling hardening coating liquid was cured for 5 seconds under the conditions of 12 m / min to form a hardened layer, and a wear-resistant antifouling hardened film was preliminarily obtained.

[0064] Then secondary UV curing, curing conditions: UV radiation is 1000mJ / cm 2 , and irradiated and cured for 2 seconds at a walking speed of 15 m / min to obtain the wear-resistant and anti-fouling hardened film of the present invention.

[0065] Example 3

[0066] 15 parts by mass of acrylate monomer (dipentaerythritol hexaacrylate) was added to a mixture of 25 parts by mass of propylene glycol monomethyl ether, 20 parts by mass of ethanol, and 5 parts by mass of methyl ethyl ketone, and 2 parts by mass of silicon oxide particles (MEK-AC-4130Y) with a particle size of 40 to 50 nm were added, and the mixture was fully stirred under an ultrasonic environment;

[0067] Then, 20 parts by mass of photocurable acrylic resin (15 parts by mass of ethylene glycol diacrylate, 5 parts by mass of 1,4-butanediol diacrylate), 2 parts by mass of photoinitiator 184, 4 parts by mass of polyethylene oxide, 0.8 parts by mass of Polyflow No. 75 and 3 parts by mass of perfluoropolyether (OPTPPL antifouling agent) were added to the mixed liquid and stirred thoroughly to obtain an antifouling hardening coating liquid.

[0068] The prepared antifouling hardening coating liquid was then coated on a PET substrate with a thickness of 125 μm, and then dried at a temperature of 80°C for 7 minutes, and then irradiated with an ultraviolet high-pressure mercury lamp at an ultraviolet radiation dose of 1200 mJ / cm 2 The antifouling hardening coating liquid was cured for 5 seconds under the conditions of 12 m / min to form a hardened layer, and a wear-resistant antifouling hardened film was preliminarily obtained.

[0069] Then secondary UV curing, curing conditions: UV radiation is 1000mJ / cm 2 , and irradiated and cured for 2 seconds at a walking speed of 15 m / min to obtain the wear-resistant and anti-fouling hardened film of the present invention.

[0070] Example 4

[0071] 15 parts by mass of acrylate monomer (dipentaerythritol hexaacrylate) was added to a mixture of 25 parts by mass of propylene glycol monomethyl ether, 20 parts by mass of ethanol, and 5 parts by mass of methyl ethyl ketone, and 2 parts by mass of silicon oxide particles (MEK-AC-4130Y) with a particle size of 40 to 50 nm were added, and the mixture was fully stirred under an ultrasonic environment;

[0072] Then, 20 parts by mass of photocurable acrylic resin (15 parts by mass of ethylene glycol diacrylate, 5 parts by mass of 1,4-butanediol diacrylate), 2 parts by mass of photoinitiator 184, 4 parts by mass of Toyo Ink LAS1513-18, 0.5 parts by mass of W001 and 2 parts by mass of perfluoropolyether (OPTPPL antifouling agent) were added to the mixed liquid and stirred thoroughly to obtain an antifouling hardening coating liquid.

[0073] The prepared antifouling hardening coating liquid was then coated on a PET substrate with a thickness of 125 μm, and then dried at a temperature of 80°C for 7 minutes, and then irradiated with an ultraviolet high-pressure mercury lamp at an ultraviolet radiation dose of 1200 mJ / cm 2 The antifouling hardening coating liquid was cured for 5 seconds under the conditions of 12 m / min to form a hardened layer, and a wear-resistant antifouling hardened film was preliminarily obtained.

[0074] Then secondary UV curing, curing conditions: UV radiation is 1000mJ / cm 2 , and irradiated and cured for 2 seconds at a walking speed of 15 m / min to obtain the wear-resistant and anti-fouling hardened film of the present invention.

[0075] Comparative Example 1

[0076] The difference between this comparative example and Example 1 is that 3 parts of polyetheresteramide (antistatic agent) are missing, and the rest are the same.

[0077] Comparative Example 2

[0078] The difference between this comparative example and Example 1 is that 0.3 parts of organosiloxane polymer KP341 (surfactant) is missing, and the rest is the same.

[0079] Comparative Example 3

[0080] The difference between this comparative example and Example 1 is that the antistatic agent is 1 part by mass, the organosiloxane polymer KP341 (surfactant) is 0.1 part, and the rest is the same.

[0081] Comparative Example 4

[0082] The difference between this comparative example and Example 1 is that the antistatic agent is 6 parts by mass, the organosiloxane polymer KP341 (surfactant) is 1 part, and the rest is the same.

[0083] Comparative Example 5

[0084] The difference between this comparative example and Example 1 is that the metal oxide particles are missing, and the rest are the same.

[0085] Comparative Example 6

[0086] The difference between this comparative example and Example 1 is that there is no secondary curing, and the rest is the same.

[0087] The wear-resistant and antifouling hardened films prepared in the above examples and comparative examples were subjected to the following performance tests:

[0088] Pencil hardness test: According to the test method of GB / T6729, the pencil hardness of the wear-resistant and anti-fouling hardened film is tested.

[0089] Eraser wear test: On the wear tester, a Korean minoan rubber strip (RUBBER wear test eraser 6X150MM red 400212000C) was selected for reciprocating friction with a load of 1000g.

[0090] Steel wool wear test: Tested in accordance with national standard ASTM D4157.

[0091] Water contact angle test: Use an optical contact angle meter to detect the surface contact angle.

[0092] Adhesion test: Tested in accordance with ASTM D 3359-09 "Adhesion by Tape Method" test standard.

[0093] Adhesion test after grinding: using a diameter of 2000-grit sandpaper was attached to the fixture; the sample was ground 20 times in a clockwise direction with a weight of 1500 g; the ground surface of the sample was then cleaned with a dust-free cloth, and the test was performed again according to the ASTM D 3359-09 "Adhesion Test by Tape Method" test standard.

[0094] Friction coefficient measurement: MXD-02 friction coefficient tester, the slider is placed in the middle area above the sample test surface, the test direction of the sample is parallel to the direction of the slider, and the readings (Us, Ud) are obtained.

[0095] Antistatic value determination: Insulation resistance measuring instrument, place it together in the sample test area and read the value directly.

[0096] The data shown in the following table are obtained.

[0097]

[0098] From the test data of the wear-resistant and antifouling hardened films prepared in Examples 1 to 4 in the above table, it can be seen that the eraser wear resistance reaches more than 2000 times, the initial water drop angle reaches more than 110°, and after the eraser is rubbed 1000 times, the water drop angle reaches 101-112°; and the adhesion test reaches 5B after grinding.

[0099] The test data of the wear-resistant and antifouling hardened films prepared from Example 1, Comparative Example 1 and Comparative Example 2 in the above table show that: lacking an antistatic agent or surfactant, the wear resistance deteriorates by less than 1500 times, and the water contact angle after 1000 times of eraser friction is much lower than 101° of Examples 1-4.

[0100] The test data of the wear-resistant and antifouling hardened films obtained from Example 1, Comparative Example 3 and Comparative Example 4 in the above table show that when the antistatic agent or surfactant is higher or lower than the specified value, the wear resistance deteriorates, and the water contact angle after rubbing with an eraser 1000 times is lower than 101°, which is much lower than that of Examples 1-4.

[0101] From the test data of the wear-resistant and antifouling hardened films prepared in Example 1 and Comparative Example 5 in the above table, it can be seen that the hardness is poor due to the lack of metal oxide particles.

[0102] From the test data of the wear-resistant and antifouling hardened films prepared in Example 1 and Comparative Example 6 in the above table, it can be seen that due to the lack of a secondary curing process, the adhesion becomes poor, and the adhesion after grinding is only 2B.

[0103] In addition, the inventor accidentally discovered through a large number of tests that the metal oxide particles, antistatic agent and surfactant (i.e. the metal oxide particles, antistatic agent and surfactant in the present invention) selected in a specific range cooperate to enhance the wear resistance and meet multiple wear resistance standards. When other metal oxide particles, antistatic agents and surfactants are selected, multiple wear resistance standards cannot be met, and the standard of more than 101 ° of water contact angle cannot be met after 1000 times of the eraser wear resistance test.

[0104] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.

[0105] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A wear-resistant and antifouling hardened film, characterized in that: It includes a substrate layer and an antifouling hardening layer disposed on one side of the substrate layer; The antifouling hardening layer is prepared by a precision coating process of an antifouling hardening coating liquid, wherein the antifouling hardening coating liquid comprises the following raw material components by weight: 20 to 30 parts of a photocurable acrylic resin, 15 to 20 parts of an acrylic acid ester monomer, 2 to 6 parts of metal oxide particles, 1.5 to 4 parts of an antistatic agent, 0.3 to 0.8 parts of a surfactant, 1 to 3 parts of an antifouling agent, 2 to 4 parts of a photoinitiator, and 30 to 55 parts of a solvent; The antifouling hardened film can withstand more than 2000 eraser abrasion tests, and after 1000 eraser abrasion tests, its water contact angle reaches more than 101°.

2. The wear-resistant and antifouling hardened film according to claim 1, characterized in that: The photocurable acrylic resin is at least one of ethylene glycol diacrylate, 1,3-butanediol diacrylate, 1,4-butanediol diacrylate, 1,6-hexanediol diacrylate and 1,9-nonanediol.

3. The wear-resistant and antifouling hardened film according to claim 1, characterized in that: The acrylate monomer is at least one of diacrylate, trimethylolpropane triacrylate, ditrimethylolpropane tetraacrylate, pentaerythritol triacrylate and dipentaerythritol hexaacrylate.

4. The wear-resistant and antifouling hardened film according to claim 1, characterized in that: The metal oxide particles are at least one of nano-aluminum dioxide particles and nano-silicon dioxide particles.

5. The wear-resistant and antifouling hardened film according to claim 1, characterized in that: The antistatic agent is at least one of polyethylene oxide, polyether ester amide and polyquaternary ammonium salt.

6. The wear-resistant and antifouling hardened film according to claim 1, characterized in that: The surfactant is at least one of an organic siloxane polymer, an acrylic polymer, an acrylic copolymer, a methacrylic polymer and a methacrylic copolymer.

7. The wear-resistant and antifouling hardened film according to claim 1, characterized in that: The antifouling agent is a modified perfluoropolyether containing unsaturated double bonds.

8. The wear-resistant and antifouling hardened film according to claim 1, characterized in that: The photoinitiator is at least one of 1-hydroxycyclohexyl phenyl ketone, 2-methyl-1-(4-methylthiophenyl)-2-morpholinyl-1-propanone, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide and 2-hydroxy-methylphenylpropane-1-one.

9. The wear-resistant and antifouling hardened film according to claim 1, characterized in that: The solvent is at least one of ethyl acetate, butanone, cyclohexanone, toluene, methyl isobutyl ketone, butyl acetate, methyl ethyl ketone, ethanol, isopropanol, methanol and propylene glycol monomethyl ether.

10. A process for preparing a wear-resistant and antifouling hardened film according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1, adding metal oxide particles to a mixed system of acrylate monomer and solvent, and mixing them evenly to obtain a premixed solution; S2, adding a photocurable acrylic resin, a photoinitiator, an antistatic agent, a surfactant and an antifouling agent to the premixed liquid, and mixing them evenly to obtain an antifouling hardening coating liquid; S3, coating the antifouling hardening coating liquid on the substrate layer, and obtaining an incompletely cured wear-resistant antifouling hardened film after drying and first UV curing; S4, subjecting the incompletely cured wear-resistant and antifouling hardened film to a second ultraviolet curing to obtain the antifouling hardened film; Among them, nitrogen protection is required during the first UV curing in step S3 to control the oxygen concentration, and the oxygen concentration is ≤300ppm. Nitrogen protection is not required for the second UV curing in step S4.